Pengaruh Adopsi FinTech, Financial Literacy, dan Financial Inclusion terhadap Kinerja UMKM melalui Daya Saing di Kota Jakarta Utara - Jihad Ihsan Ramadan (Jurnal EMT KITA, 2026)
The rapid development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to improve their competitiveness and business performance. This study aims to analyze the effect of fintech adoption, financial literacy, and financial inclusion on MSME performance through competitiveness as a mediating variable among MSMEs in North Jakarta. This research employed a quantitative approach with a causal design. Data were collected from 300 MSME owners and managers using a structured questionnaire with a five-point Likert scale. The sampling technique used was purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that financial literacy and financial inclusion have a positive and significant effect on competitiveness, while fintech adoption does not significantly affect competitiveness. Furthermore, fintech adoption, financial literacy, and competitiveness significantly influence MSME performance, whereas financial inclusion has no direct effect on MSME performance. Mediation analysis reveals that competitiveness does not mediate the relationship between fintech adoption and MSME performance. However, competitiveness partially mediates the relationship between financial literacy and MSME performance as well as between financial inclusion and MSME performance. The findings suggest that improving financial literacy and financial inclusion can strengthen MSME competitiveness and ultimately enhance business performance. Therefore, policymakers and financial institutions should encourage financial education and expand access to financial services for MSMEs.